Organic acidurias: major gaps, new challenges, and a yet unfulfilled promise - Dimitrov, Bianca; Molema, Femke; Williams, Monique; Schmiesing, Jessica; Mühlhausen, Chris; Baumgartner, Matthias R.; Schumann, Anke; Kölker, Stefan (Journal of inherited metabolic disease, 2021)
Organic acidurias (OADs) comprise a biochemically defined group of inherited metabolic diseases. Increasing awareness, reliable diagnostic work-up, newborn screening programs for some OADs, optimized neonatal and intensive care, and the development of evidence-based recommendations have improved neonatal survival and short-term outcome of affected individuals. However, chronic progression of organ dysfunction in an aging patient population cannot be reliably prevented with traditional therapeutic measures. Evidence is increasing that disease progression might be best explained by mitochondrial dysfunction. Previous studies have demonstrated that some toxic metabolites target mitochondrial proteins inducing synergistic bioenergetic impairment. Although these potentially reversible mechanisms help to understand the development of acute metabolic decompensations during catabolic state, they currently cannot completely explain disease progression with age. Recent studies identified unbalanced autophagy as a novel mechanism in the renal pathology of methylmalonic aciduria, resulting in impaired quality control of organelles, mitochondrial aging and, subsequently, progressive organ dysfunction. In addition, the discovery of post-translational short-chain lysine acylation of histones and mitochondrial enzymes helps to understand how intracellular key metabolites modulate gene expression and enzyme function. While acylation is considered an important mechanism for metabolic adaptation, the chronic accumulation of potential substrates of short-chain lysine acylation in inherited metabolic diseases might exert the opposite effect, in the long run. Recently, changed glutarylation patterns of mitochondrial proteins have been demonstrated in glutaric aciduria type 1. These new insights might bridge the gap between natural history and pathophysiology in OADs, and their exploitation for the development of targeted therapies seems promising.
First published: 15 May 2020
Gesehen am 01.03.2021